Analisis Pengaruh Penerapan Office Channeling Terhadap Penambahan Dana Pihak Ketiga Pada Bank DKI Syariah - Agus Wismo Widodo (Fakultas Teknik Universitas Persada Indonesia YAI, 2020)
The research objective was to determine the optimization of the application of office channeling at Bank DKI Syariah, Wahid Hasyim Branch. The process of collecting data uses library data and field data by means of observation, interviews, and documentation. The results showed that the application of office channeling services was still limited to collecting third party funds, namely savings, current accounts and time deposits. The supporting factor in the application of Office channeling is having a fairly extensive network in the DKI area and has been supported by adequate information technology. The inhibiting factors of the lack of socialization and education to the public, and the non-recognition of the achievement of Office channeling as part of the business performance achievement of implementing Bank DKI Syariah Office channeling can increase third party funds, increase market share, expand service access to the public and can compete with conventional banks. The research implication is expected that DKI Syariah Bank can improve service quality, both in terms of service and products in the sharia channeling office. Bank DKI as the office in determining targets and achieving business performance so as to encourage maximum growth of funds.